1978
DOI: 10.1099/00221287-109-2-245
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas savastanoi and Other Bacteria Colonizing the Surface of Olive Leaves in the Field

Abstract: There were characteristic seasonal fluctuations in the populations of most of the bacteria. The abundance of P. savastanoi on healthy leaves in April and October supports earlier suggestions that the phylloplane of the host may be an important source of readily available inoculum in the epidemiology of olive knot disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 44 publications
2
69
0
1
Order By: Relevance
“…There are few studies on the epidemiology of olive knot disease and most data of epiphytic Psv populations on the aerial surface of the tree come from studies done in southern Italy (Ercolani, 1971(Ercolani, , 1978(Ercolani, , 1979(Ercolani, , 1983(Ercolani, , 1985(Ercolani, , 1991(Ercolani, , 1993 and southeastern Spain (Quesada et al, 2007;Quesada et al, 2010a;2010b). In the aforementioned studies, epiphytic Psv populations in the phyllosphere of olive trees were estimated by washing, followed by plating serial dilution of the washings.…”
Section: Epiphytic Populations Of Psvmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies on the epidemiology of olive knot disease and most data of epiphytic Psv populations on the aerial surface of the tree come from studies done in southern Italy (Ercolani, 1971(Ercolani, , 1978(Ercolani, , 1979(Ercolani, , 1983(Ercolani, , 1985(Ercolani, , 1991(Ercolani, , 1993 and southeastern Spain (Quesada et al, 2007;Quesada et al, 2010a;2010b). In the aforementioned studies, epiphytic Psv populations in the phyllosphere of olive trees were estimated by washing, followed by plating serial dilution of the washings.…”
Section: Epiphytic Populations Of Psvmentioning
confidence: 99%
“…These bacteria would be incorporated to the knot subsequently to the infection caused by the etiologic agent, according to García de los Ríos (1989). Indeed, a symbiotic relationship may exist between Psv and Pantoea (or may be other bacteria) because they are found together not only in knots but also as epiphytic bacteria in infected plants (Ercolani, 1978(Ercolani, , 1991Quesada et al, 2007). Furthermore, preliminary tests have shown that strains of an uncharacterized Erwinia, isolated from Psv-related olive knots, could have a synergistic effect with Psv in the development of typical symptoms of olive knot disease (Fernandes & Marcelo, 2002).…”
Section: Epidemiology and Control Of Plant Diseases Caused By Phytopamentioning
confidence: 99%
“…The following crops were sampled near Trinitapoli, Molfetta, Monopoli, Castellana Grotte and Scanzano Jonico, in the SE of Italy, where they were grown commercially during the spring (sp), summer (su), autumn (au) or winter (wi) in 1991 strokes of 3 cm min-') at room temperature in the dark for 2 h (Ercolani 1978). After transfer of the flask into an anaerobic cabinet (mod.…”
Section: Plant Materials From the Fieldmentioning
confidence: 99%
“…Separate counts for each colony type were made under a Controls using the suspending and plating media indicated above and the procedures described elsewhere (Ercolani 1978) failed to detect spores inside the leaves and showed that over 90°/o of the spores on the phylloplane were washed off into the peptone water under the conditions described above.…”
Section: Plant Materials From the Fieldmentioning
confidence: 99%
“…Esse habitat pode variar a extremos de temperatura e exposição ultravioleta em prazos muito curtos (DICKINSON et al, 1975;ERCOLANI, 1978ERCOLANI, , 1991JACQUES et al, 1995 Para que se possa combater ou se adaptar a esses impactos, um primeiro passo importante é buscar conhecê-los, definindo-se cenários agrícolas a partir de cenários futuros das mudanças climáticas.…”
Section: Filosferaunclassified